Birth month as a risk factor of allergic diseases: Analysis of database of about 50 thousand children - Alexander Pampura; Natalia Esakova; Daria Dolotova; Olga Serebryakova; Nikita Chikunov (PLoS ONE, 2025)
Background The season of birth is a factor influencing the child during the neonatal adaptation period and potentially affecting the risk of allergies. The objective of this study was to ascertain the association between the month of birth and the subsequent development of allergic diseases in Moscow children, Russia. Methods in 2024 the de-identified data from medical records and parental questionnaires of 49,857 children under the age of 18 was retrieved from the Moscow Unified Medical Information and Analytical System. The database contained the information regarding the presence of atopic dermatitis, asthma, allergic rhinitis, age, sex and family history of allergies. The statistical processing involved the calculation of crude odds ratio (cOR), adjusted odds ratio (aOR) based on multivariate logistic regression. Results the odds of allergic rhinitis among children born between October and April was found to be significantly higher in comparison to July (reference), with the strongest association observed for December (aOR, 1,342; 95% CI, 1,203−1,497), January (aOR, 1,386; 95% CI, 1,243−1,546) and February (aOR, 1,371; 95% CI, 1,226−1,533). In these months, the odds were 34−38% higher than in July. The odds of atopic dermatitis among children born between August and February was significantly higher compared to April (reference), the greatest association observed for October (aOR, 1,169; 95% CI, 1,059−1,291), with the association being 16% higher than for April. Conclusion This is the first study in Russia to demonstrate that children born in October in Moscow face elevated odds of atopic dermatitis, while children born in December, January, and February are more susceptible to allergic rhinitis. The association detected was independent of sex, age, family allergic history and combination of allergic diseases, which merits further investigation.